The Role of Faith-Based Organizations in Promoting Justice for Refugees and Migrants in Indonesia (Indonesian Theological Justice Review, 2025)
Indonesia, as a transit and destination country for refugees and migrants, faces significant challenges in ensuring the protection and well-being of these vulnerable populations. This paper examines the role of faith-based organizations (FBOs) in advocating for justice, human rights, and the social integration of refugees and migrants in Indonesia. Drawing from Islamic, Christian, and interfaith perspectives on hospitality, justice, and human dignity, the study explores how religious teachings motivate FBOs to provide humanitarian aid, legal assistance, and social services to refugees and migrants. The paper analyzes the impact of key FBOs working with refugee populations, focusing on initiatives that provide shelter, healthcare, education, and vocational training. It also examines the theological underpinnings of these efforts, such as Christian principles of hospitality and Islamic teachings on helping the oppressed. The paper argues that FBOs play a crucial role in filling gaps in Indonesia’s refugee protection system, often operating in areas where government services are limited. However, the research also highlights the challenges that FBOs face, including limited resources, political pressures, and legal constraints. Recommendations include strengthening partnerships between religious organizations, the government, and international agencies to create a more effective and just response to the needs of refugees and migrants in Indonesia.